2007
DOI: 10.1038/sj.eye.6703013
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer measurements and optic nerve head analysis in multiple sclerosis patients

Abstract: Purpose To verify whether scanning laser polarimeter with the new variable corneal compensation algorithm (GDx VCC) and scanning laser ophthalmoscopy (Heidelberg Retina Tomograph (HRT)) allow measuring retinal ganglion cell loss in patients with multiple sclerosis (MS). Patients and methods We enrolled 23 MS patients with a history of previous demyelinating monocular optic neuritis. Examination included visual evoked potentials (VEPs), scanning laser ophthalmoscopy, and scanning laser polarimeter. HRT was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
2
13
0
2
Order By: Relevance
“…25 Also, some studies found increased P100 latency in MS eyes: not only in patients with ON, but also in those without a history of previous ON. 10,11,[26][27][28] In our study, we found significant prolonged P100 latency similar to the results of the above studies. Most of the previous studies have demonstrated a decrease in P100 wave amplitudes in MS eyes compared with controls.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…25 Also, some studies found increased P100 latency in MS eyes: not only in patients with ON, but also in those without a history of previous ON. 10,11,[26][27][28] In our study, we found significant prolonged P100 latency similar to the results of the above studies. Most of the previous studies have demonstrated a decrease in P100 wave amplitudes in MS eyes compared with controls.…”
Section: Discussionsupporting
confidence: 82%
“…The usefulness of VEP for evaluation of abnormalities in the anterior visual pathway in MS patients has been reported in several previous studies dating back several years. 10,11,[25][26][27][28] Weinstock-Guttman et al evaluated 37 MS patients and found prolonged P100 latency in 75% of them. 25 Also, some studies found increased P100 latency in MS eyes: not only in patients with ON, but also in those without a history of previous ON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study, Iester et al (2007) reported that GDx is able to detect loss of ganglion cells following demyelinating optic neuritis in MS patients and that, as we observed, there is good correlation between VEP abnormalities and some GDx parameters.…”
Section: Discussionmentioning
confidence: 49%
“…1-3 RNFL loss is not specifi c to glaucoma. Recent literature reports indicate that the GDx VCC demonstrates decreases in RNFL thickness in patients with optic neuritis (ON), [4][5][6] but that visual evoked potential (VEP) or static perimetry is superior to the GDx VCC in detecting early damage of ON in patients with multiple sclerosis (MS). 7 This study evaluated the structural changes in peripapillary RNFL using the GDx VCC in patients with ON resulting from MS and compared them with those of healthy subjects.…”
Section: Introductionmentioning
confidence: 98%